Jurisdictional Conflict in Nigeria: Applying Berebon's Pluralist Complementarity Model - Charles Berebon (Pinisi Journal of Social Science, 2026)
Nigeria's legal system is characterized by a complex pluralism in which customary courts, Sharia courts, and state courts operate simultaneously, often with overlapping jurisdiction and inconsistent outcomes. This jurisdictional fragmentation has produced significant challenges for litigants, legal practitioners, and the judiciary. The absence of clear mechanisms for coordinating the outputs of these different legal orders has created an environment where powerful actors can forum-shop, where vulnerable parties are often disadvantaged, and where the legitimacy of the legal system as a whole is undermined. This paper applies the pluralist complementarity model developed by Berebon (2025a, 2025b, 2025c) within his broader theory of Communitarian Legal Pluralism to the specific context of Nigeria's jurisdictional conflicts between customary courts and state courts. Drawing on doctrinal legal analysis, case law examination, and interviews with legal practitioners, the paper identifies the primary sources of jurisdictional conflict, including the repugnancy clause, the lack of clear jurisdictional boundaries, and the absence of effective coordination mechanisms. The paper demonstrates how Berebon's principles of subsidiarity, recognition and coordination, and dynamic adaptation can guide the design of institutional reforms to resolve these conflicts. The paper proposes specific reforms, including the establishment of jurisdictional interfaces, the development of cross-court evidentiary protocols, and the creation of appellate coordination mechanisms. The findings have implications for judicial reform, access to justice, and legal pluralism in Nigeria and similar contexts across Africa.